Phthalate esters in atmospheric PM2.5 and PM10 in the semi-arid city of Xi'an, Northwest China: Pollution characteristics, sources, health risks, and relationships with meteorological factors. (March 2020) - Ma, Bianbian; Wang, Lijun; Tao, Wendong; Liu, Mengmei; Zhang, Panqing; Zhang, Shengwei; Li, Xiaoping; Lu, Xinwei
Abstract: PM2.5 and PM10 samples were collected in the semi-arid city of Xi'an in Northwest China from November 2016 to November 2017 and analyzed to assess pollution characteristics, sources, health risks, and influencing factors of 6 priority phthalate esters (PAEs). The results showed that the sum of the 6 PAEs (Σ6 PAEs) was 85.5 ng m −3 in PM2.5 and 94.5 ng m −3 in PM10, being higher at the suburban site than the urban site and winter > spring > summer > autumn. The most abundant PAE was bis(2-ethylhexyl phthalate) (DEHP). PM2.5 - and PM10 -bound PAEs were associated mainly with the use of plasticizers plus the uses of cosmetics and personal care products, construction materials, and home furnishings. Temperature, relative humidity, and visibility had stronger influences on the concentrations of PM and PM-bound PAEs than pressure and wind speed. Pressure and relative humidity were positively correlated with the concentrations of PM and most of the PM-bound PAEs, while temperature, visibility and wind speed had negative correlations with the concentrations of PM and PM-bound PAEs. The non-carcinogenic risks of human inhalation exposure to PM-bound PAEs were in the range of 10 −7 to 10 −3, suggesting low non-cancer risks, which were higher at the suburban site than the urban site and higher to children than adults. The cancer risks of human inhalation exposure to PM-bound DEHP and butyl benzyl phthalate (BBP) were in the range of 10 −12 to 10 −10, suggesting low carcinogenic risks, being in the order of the suburban site > the urban site and DEHP > BBP. Special attention should be paid to long-term low dose exposure to PAEs in the suburb, especially in winter and spring. Graphical abstract: Image 1 Highlights: PM2.5 - and PM10 -bound PAEs were studied in the semi-arid city of Xi'an in China. PM and PM-bound PAE levels were higher in suburb, especially in winter and spring. PM-bound PAEs were mainly dominated by bis(2-ethylhexyl phthalate). Meteorological conditions had important influences on PM and PM-bound PAEs contents. Special concern should be paid to long-term low dose exposure to PM-bound PAEs.